Facial trauma epidemiology: etiologic factor relevance on lesions gravity - Angarani, Germano; Cunha, Laryssa Queiroz; Brito, Lucas Teixeira; Silveira, Rubens Jorge; Prata-Júnior, Agnaldo Rocha; Izac, Ângela Beatriz Cavalcante Amorim; Goulart, Douglas Rangel (Journal of Oral Diagnosis, 2022)
The aims of this study were to describe the epidemiological characteristics of patients treated at a Maxillofacial Surgery service, to know the etiological factors involved in the trauma mechanism of patients under hospital treatment and to relate the importance of these factors in the severity of the injuries. A retrospective study was carried out of 1510 medical records of all patients who were hospitalized with facial trauma in a Midwest region of Brazil trauma referral hospital. Descriptive and comparative statistical analysis were performed using SPSS 18.0 software. Data were compared using the chi-square test, results were considered statistically significant for values of p <0.05. The mean age of the patients was 32.61 (SD = 17.08) and the extremes of age ranged from 7 months of life to 94 years. Men were more affected by facial trauma than women, with a male:female ratio of 4.3:1 and means of transport were the most prevalent etiological factor (53.3%). Motorcycle’s accidents being associated with a higher prevalence of combined fractures (P <0.01), while sports accidents had a higher incidence of single injuries. Based on the results, it is possible notice that some activities still have a difference in prevalence between men and women and that this affects the exposure to etiological factors of facial trauma. Etiological factors may be associated with the extent and severity of injuries resulting from facial trauma. Keywords: Maxillofacial Injuries; Trauma Centers; Epidemiology.